ASESMEN KESIAPAN SEKOLAH SD DAN PEMBUATAN SISTEM INFORMASI UNTUK PELAPORAN HASIL ASESMEN - Astuti, Ratri Sunar; Polina, Agnes Maria; Etikawati, Agnes Indar; Suprawati, MM.Nimas Eki (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
As affected by Covid-19 pandemic, most of children experienced online learning. This online learning could affect children school readiness when they entering school. They showed various problems, such as math, writing, emotion, attention and in following instructions. To assist these children, teachers need to assess their school readiness using NST, and their intellectual potential using CPM. As the assessment process often takes time, we developed an information system integrated in this assessment. This system enables the psychologists to reduce time in doing the assessment and teachers may get the result faster. Based on the assessment using NST and CPM, it was found that in general children are ready to enter the school.